Investigating Reclaim Australia and Britain First’s Use of Social Media: Developing a New Model of Imagined Political Communities Online - Lella Nouri (Journal for Deradicalization, 2019)
Against a backdrop of widespread concern regarding the extreme right’s increasing use of social media and using a combination of quantitative and qualitative linguistic techniques, this paper reports the results of the first systematic analysis of how two extreme right groups (Britain First and Reclaim Australia) construct themselves as sui generis ‘imagined political communities’ on social media (Facebook and Twitter). Analysis of a circa 5-million-word dataset reveals that both groups strategically mobilise a number of topical news events (relative to their country) and systematically denigrate (‘other’) immigrants and Muslims. It also reveals that Reclaim Australia favours more aggressive stances than Britain First towards targeted out-groups. The relative salience and inter-relations between the features that form these groups’ imagined political communities differ significantly from those proposed by pre-digital era notions of imagined political communities. Thus, this study proposes a new model of social—media based imagined political communities for extreme right groups in which developing boundaries against perceived threats posed by othered groups (Muslims and immigrants) emerges as the main pillar.